2021
DOI: 10.1039/d1ta02639a
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of the in-plane crack formation of O3-Na0.8Mg0.2Fe0.4Mn0.4O2 due to oxygen gas evolution for Na-ion batteries

Abstract: Crack formation is considered one of the significant failure modes of layered oxide cathode materials for Na-ion batteries because particle cracks accelerate electrolyte decomposition, transition metal dissolution, and electrical contact...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…This adverse TM migration is prone to concurrently shrink the interlayer spacing and trigger the layered-to-spinel or rock-salt transformation, leading to a greatly reduced degree of Na + diffusion and finally inducing the degradation cascade of cell performance. 10–12…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This adverse TM migration is prone to concurrently shrink the interlayer spacing and trigger the layered-to-spinel or rock-salt transformation, leading to a greatly reduced degree of Na + diffusion and finally inducing the degradation cascade of cell performance. 10–12…”
Section: Introductionmentioning
confidence: 99%
“…This adverse TM migration is prone to concurrently shrink the interlayer spacing and trigger the layered-to-spinel or rock-salt transformation, leading to a greatly reduced degree of Na + diffusion and nally inducing the degradation cascade of cell performance. [10][11][12] Aside from controlling the cut-off voltage, the most common strategy for mitigating such pernicious effects is chemical substitution on the TM sites. [13][14][15] Numerous previous studies have demonstrated that introducing dopants to tune the electronic transfer and structural characteristics indeed denotes creditable efficaciousness for stabilizing the structure at high states of charge and realizing high-capacity batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Among various sodium cathode candidates, layered transition metal oxides Na x TMO 2 (where TM refer to transition metal ion) have attracted much attention due to its advantages such as high specific capacity, simple preparation, and environmental friendliness. Compared with P2- and P3-type layered oxides, the sufficient sodium content enables O3-type layered oxides to be advantageous over counterparts in full-cell applications. However, their cycle life is still subject to undesired structural degradation caused by transition metal slab sliding upon charging to high voltages (>4 V), leading to fast capacity decay and poor cycling stability in NIBs. In addition, most O3-type materials suffer from notable performance deterioration when storing in a humid environment, which undoubtedly increases their cost of transportation and preservation. ,, For O3-NaNi 0.5 Mn 0.5 O 2 , when the charging cutoff voltage is greater than 4.1 V, its specific capacity is up to 180 mAh g –1 . , However, a series of complex phase transitions (O3–O′3–P3–P′3–P3′–O1) cause significant internal stress, leading to the collapse of layered structure, resulting in capacity decay and poor rate performance. ,, In addition, when O3-NaNi 0.5 Mn 0.5 O 2 was exposed to air for 2 h, the structure changed from O3 phase to O′3- and P3-Na 1– y Ni 0.5 Mn 0.5 O 2 , which also leads to the degradation in electrochemical performance. , Undoubtedly, further practical application of O3-type layered oxides for NIBs requires addressing both phase transition reversibility during deep desodiation and humid sensitivity when exposed to ambient air.…”
Section: Introductionmentioning
confidence: 99%
“…Li-excess DRS oxides have attracted tremendous research interest in recent years 8–23 owing to their high capacity of above 350 mA h g −1 , 24 which has been explained by the unexpected anionic redox. 25–28 Li-intercalated V 2 O 5 (Li x V 2 O 5 ) is of particular interest among the DRS oxides.…”
Section: Introductionmentioning
confidence: 99%